Stochastic suicide substrate reaction model - Zafar, Zain Ul Abadin; İnç, Mustafa; Tchier, Fairouz; Akinyemi, Lanre (Elsevier, 2023)
Nowadays, numeric paradigms have great significance in every field especially for solving the NDEs, PDEs, biochemical reactions etc. Here, we represent a realistic suicide substrate reaction specimen which can be represented by a system with four equations for the concentrations of the numerous molecules as functions of time. We present a technique to attain exact, approximate elucidations using the stochastic theory. This systematic technique provides more realistic numeric elucidations than other techniques which have been offered. Unfortunately, the numeric techniques like Euler-Maruyama, stochastic Euler, and stochastic RK4 fail for large step sizes. Stochastic nonstandard finite difference technique (SNSFD) has been fabricated for the suicide substrate reaction specimen and numeric tests are executed for diverse values of discretization parameter 'h'. The consequences are matched with a well-known numeric scheme.(c) 2022 Elsevier B.V. All rights reserved.
Keywords: Stochastic suicide substrate (SSS) reaction; model; Stochastic differential equations (SDEs); Stochastic NSFD scheme; Stochastic RK4 (SRK-4) scheme; Euler-Maruyama scheme (EMS); Stochastic Euler scheme (SES)